How Do You Build a “Culture of Health”? A Critical Analysis of Challenges and Opportunities from Medical Anthropology - Mason, Katherine A. (Popul Health Manag, 2020)
The Robert Wood Johnson Foundation's Culture of Health Action Framework aims to “make health a shared value” and improve population health equity through widespread culture change. The authors draw upon their expertise as anthropologists to identify 3 challenges that they believe must be addressed in order to effectively achieve the health equity and population health improvement goals of the Culture of Health initiative: clarifying and demystifying the concept of “culture,” contextualizing “community” within networks of power and inequality, and confronting the crises of trust and solidarity in the contemporary United States. The authors suggest that those who seek to build a “Culture of Health” refine their understanding of how “culture” is experienced, advocate for policies and practices that break down unhealthy consolidations of power, and innovate solutions to building consensus in a divided nation.